RICTOR amplification is associated with Rictor membrane staining and does not correlate with PD-L1 expression in lung squamous cell carcinoma - Ildikó Krencz; Dániel Sztankovics; Anna Sebestyén; Judit Pápay; Titanilla Dankó; Dorottya Moldvai; Elmar Lutz; Andras Khoor (Frontiers Media S.A., 2024)
RICTOR gene, which encodes the scaffold protein of mTORC2, can be amplified in various tumor types, including squamous cell carcinoma (SCC) of the lung. RICTOR amplification can lead to hyperactivation of mTORC2 and may serve as a targetable genetic alteration, including in lung SCC patients with no PD-L1 expression who are not expected to benefit from immune checkpoint inhibitor therapy. This study aimed to compare RICTOR amplification detected by fluorescence in situ hybridization (FISH) with Rictor and PD-L1 protein expression detected by immunohistochemistry (IHC) in SCC of the lung. The study was complemented by analysis of the publicly available Lung Squamous Cell Carcinoma (TCGA, Firehose legacy) dataset. RICTOR amplification was observed in 20% of our cases and 16% of the lung SCC cases of the TCGA dataset. Rictor and PD-L1 expression was seen in 74% and 44% of the cases, respectively. Rictor IHC showed two staining patterns: membrane staining (16% of the cases) and cytoplasmic staining (58% of the cases). Rictor membrane staining predicted RICTOR amplification as detected by FISH with high specificity (95%) and sensitivity (70%). We did not find any correlation between RICTOR amplification and PD-L1 expression; RICTOR amplification was detected in 18% and 26% of PD-L1 positive and negative cases, respectively. The TCGA dataset analysis showed similar results; RICTOR copy number correlated with Rictor mRNA and protein expression but showed no association with PD-L1 mRNA and protein expression. In conclusion, the correlation between RICTOR amplification and Rictor membrane staining suggests that the latter can potentially be used as a surrogate marker to identify lung SCC cases with RICTOR amplification. Since a significant proportion of PD-L1 negative SCC cases harbor RICTOR amplification, analyzing PD-L1 negative tumors by RICTOR FISH or Rictor IHC can help select patients who may benefit from mTORC2 inhibitor therapy.